EFFECTIVENESS OF ROBUSTA COFFEE BEAN EXTRACT GEL ON COLLAGEN FIBERS DENSITY IN POST-GINGIVECTOMY WOUND HEALING - Ermawati, Tantin; Harmono, Happy; Kartikasari, Dania (Odonto : Dental Journal, 2021)
Background: Gingivectomy is a periodontal surgical procedure that eliminates excess gingival tissues by excision, usually to remove a gingival pocket which leads to scars and recontours the gingival to its proper anatomical form. Wound healing is a process to restore the missing functions and structures of a tissue due to injuries or inflammations. Robusta coffee bean contains many bioactive compounds that can accelerate the wound healing process. The study aimed to determinate the effectiveness of robusta coffee bean extract gel with concentration 40%,50%,60% on collagen fibers density in post-gingivectomy wound healing Method: 36 Wistar rats were divided into 9 groups: control, gingivectomy without therapy, gingivectomy +40% robusta coffee bean extract gel, gingivectomy +50% robusta coffee bean extract gel, and gingivectomy+60% robusta coffee bean extract gel. The last 4 groups were divided again into day 3 and 7 euthanasia. The results were processed by Trichrome Mallory to visualized the collagen fibers and then measured by ImageJ software.Result: Robusta coffee beans extract gel therapy with concentration 40%, 50% and 60% had higher average collagen fibers density compared to group without therapy.Conclusion: Robusta coffee bean extract gel increased the density of collagen fibers in post-gingivectomy wound healing